High-Temperature Methane Sensors Based on ZnGa2O4:Er Ceramics for Combustion Monitoring - Aleksei V. Almaev; Zhakyp T. Karipbayev; Askhat B. Kakimov; Nikita N. Yakovlev; Olzhas I. Kukenov; Alexandr O. Korchemagin; Gulzhanat A. Akmetova-Abdik; Kuat K. Kumarbekov; Amangeldy M. Zhunusbekov; Leonid A. Mochalov; Ekaterina A. Slapovskaya; Petr M. Korusenko; et al. (Technologies, 2025)
The use of CH4 as an energy source is increasing every day. To increase the efficiency of CH4 combustion and ensure that the equipment meets ecological requirements, it is necessary to measure the CH4 concentration in the exhaust gases of combustion systems. To this end, sensors are required that can withstand extreme operating conditions, including temperatures of at least 600 °C, as well as high pressure and gas flow rate. ZnGa2O4, being an ultra-wide bandgap semiconductor with high chemical and thermal stability, is a promising material for such sensors. The synthesis and investigation of the structural and CH4 sensing properties of ceramic pellets made from pure and Er-doped ZnGa2O4 were conducted. Doping with Er leads to the formation of a secondary Er3Ga5O12 phase and an increase in the active surface area. This structural change significantly enhanced the CH4 response, demonstrating an 11.1-fold improvement at a concentration of 104 ppm. At the optimal response temperature of 650 °C, the Er-doped ZnGa2O4 exhibited responses of 2.91 a.u. and 20.74 a.u. to 100 ppm and 104 ppm of CH4, respectively. The Er-doped material is notable for its broad dynamic range for CH4 concentrations (from 100 to 20,000 ppm), low sensitivity to humidity variations within the 30–70% relative humidity range, and robust stability under cyclic gas exposure. In addition to CH4, the sensitivity of Er-doped ZnGa2O4 to other gases at a temperature of 650 °C was investigated. The samples showed strong responses to C2H4, C3H8, C4H10, NO2, and H2, which, at gas concentrations of 100 ppm, were higher than the response to CH4 by a factor of 2.41, 2.75, 3.09, 1.16, and 1.64, respectively. The study proposes a plausible mechanism explaining the sensing effect of Er-doped ZnGa2O4 and discusses its potential for developing high-temperature CH4 sensors for applications such as combustion monitoring systems and determining the ideal fuel/air mixture.